Educational Research and the Socialization of Results in the Current Cuban School - Boza Oramas, Yuliannela; Escribano Hervis, Elmys; Keeling Álvarez, Mercedes (Emerging Trends in Education, 2021)
The article addresses the issue of significance for the current context of the socialization of educational research results. The objective is to argue the role of teachers and educational directors in the educational research process in the Cuban school. The article includes an essentially theoretical elaboration; this required the application of theoretical research methods, including the historical-logical, inductive-deductive and documentary analysis, which has allowed the determination of the state of the art contextualized in the educational contemporary Cuban reality. Empirical knowledge is also asserted based on the experience of participating in sessions of analysis of the subject in scientific advisory bodies, systematic exchanges with educational directors, teachers, and advisers of the Educational Scientific Activity at the level of municipalities and provinces in Cuba. The authors highlight the need for managers and teachers to carry out full-cycle educational research and timely socialize their results through various spaces and options; this is a referent for the design of policies regarding the subject.